Dinoflagellate assemblages in the west iberian upwelling region (Sagres, Portugal) during 1994–2001 - Danchenko, Sergei (2022)
Changes in the composition of dinoflagellates from 1994 to 2001 at a station influenced by wind-induced seasonal upwelling off SW Portugal were analyzed in relation to oceanography. 194 taxa of dinoflagellates were detected, the most frequent belonged to the genera Tripos, Protoperidinium, Dinophysis, Diplopsalopsis, Prorocentrum and Lingulodinium. The composition of dinoflagellate communities followed a seasonal pattern, in association with oceanographic forcing and change of upwelling conditions. Harmful species such as Dinophysis acuminata, D. acuta, D. caudata, Gonyaulax spp. and Lingulodinium polyedra were found to develop during the upwelling season, typically comprising summer and early autumn in the West Iberian upwelling system, and also occasionally in the conditions following upwelling events in other seasons.